Could Augustine have Produced a More Edifying Account of Predestination? - Rist, John (Augustiniana, 2020)
Among various apparent weaknesses in Augustine’s account of predestination are: that it makes his account of justice, wisdom and mercy unintelligible; that it leads him to be easily misinterpreted as teaching a doctrine of ‘double predestination’; that it demands inadequate interpretations of Scripture; that it suggests God’s behaviour is arbitrary. But although like all thinkers Augustine’s options are limited by the intellectual conditions in which he wrote, yet within his known writings we can recognize that he has the resources to avoid many of his apparent errors and confusions. As in improving his accounts of religious freedom and of ‘holy’ warfare, so with predestination more careful attention to his own ideas about man’s creation in God’s image, together with attention to what is now referred to as the distinction between God’s antecedent and consequent wills, would do a great deal to make his thesis about predestination more ‘edifying’.